Qur'ānic Rhetorical Questions: Their Identification and Communicative Functions - Dror, Yehudit (2021)
This article presents a grammatical framework to evaluate rhetorical questions in the Qur'ān. It is shown that the context of a rhetorical question implies its own answer, which is precisely what prevents the addressee from taking the question literally. Rhetorical questions are also treated as a type of indirect speech act. It is argued that the purpose of a rhetorical question is to cajole, convince, affirm, denounce or to express wonder or irony. By drawing on concepts and methods from Relevance Theory and Rhetorical Structure Theory (RST), it is argued that the relationship between a rhetorical question and the utterances which precede or follow it invokes the intended message, not the question itself.
Le présent article offre un cadre grammatical d’évaluation des questions rhétoriques du Coran. Le contexte d’une question rhétorique implique sa propre réponse, ce qui interdit à l’interlocuteur d’interpréter la question de façon littérale. Les questions rhétoriques sont également considérées comme un type de d’acte de langage indirect. Le but d’une question rhétorique est de convaincre, d’affirmer, de dénoncer, d’exprimer la surprise ou l’ironie. À l’aide des concepts et méthodes de la théorie de la pertinence et de la théorie de la structure rhétorique, on estime que le message se trouve dans le rapport entre la question rhétorique et les paroles qui l’encadrent, non dans la question elle-même.